Chapter Consciousness and Morality - Shepherd, Joshua (Oxford University Press, 2020)
This chapter considers three connections between consciousness and issues in ethics: first, the relevance of consciousness for questions surrounding an entity's moral status; second, the relevance of consciousness for questions surrounding moral responsibility for action; and third, the relevance of consciousness for the acquisition of moral knowledge. This is a disparate set of connections, prompting a question: is there anything about consciousness these connections have in common? One might expect the answer to be no. But debate in each area has thus far failed to settle just what about consciousness is so intuitively important for moral status, moral responsibility, and moral knowledge. Given this fact, it remains possible that there is some common connection of these different issues in ethics to consciousness. The chapter takes up this possibility in its conclusion.